Letter to Beaumont, Letters Written from the Mountain, and Related Writings - Rousseau, Jean-Jacques.; Kelly, Christopher; Grace, Eve.; Bush, Judith R. (Lebanon : Dartmouth College Press, 2013)
Rousseau's responses to the religious and political critics of his works.
Cover; Half-title; Title Page; Copyright; Contents; Preface; Chronology of Works in Volume 9; Note on the Text; Introduction; Pastoral Letter of His Grace the Archbishop of Paris; Pastoral Letter of his Grace the Archbishop of Paris; Letter to Beaumont; Fragments of the Letter to Christophe de Beaumont; History of the Government of Geneva; Letters Written from the Mountain; First Part; First Letter; Second Letter; Third Letter; Fourth Letter; Fifth Letter; Sixth Letter; Second Part; Seventh Letter; Eighth Letter; Ninth Letter; The Vision of Pierre of the Mountain, Called the Seer; Notes.
Includes index.
Description based on print version record.
Keywords: Church and state -- Early works to 1800.; Philosophy; Rousseau, Jean-Jacques, -- 1712-1778 -- Censorship; Rousseau, Jean-Jacques, -- 1712-1778 -- Censorship; Church and state -- Early works to 1800.; LITERARY CRITICISM / European / French; Electronic books